2023
DOI: 10.3390/genes14030623
|View full text |Cite
|
Sign up to set email alerts
|

Winners and Losers of Atlantification: The Degree of Ocean Warming Affects the Structure of Arctic Microbial Communities

Abstract: Arctic microbial communities (i.e., protists and bacteria) are increasingly subjected to an intrusion of new species via Atlantification and an uncertain degree of ocean warming. As species differ in adaptive traits, these oceanic conditions may lead to compositional changes with functional implications for the ecosystem. In June 2021, we incubated water from the western Fram Strait at three temperatures (2 °C, 6 °C, and 9 °C), mimicking the current and potential future properties of the Arctic Ocean. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…This species develops when cells encounter high nutrient concentrations and increased light. The dominant phytoplankton groups were found to be more affected by meltwater input than by temperature in this area [59].…”
Section: Size Distribution Of Phytoplankton Chlorophyll a Biomass And...mentioning
confidence: 79%
“…This species develops when cells encounter high nutrient concentrations and increased light. The dominant phytoplankton groups were found to be more affected by meltwater input than by temperature in this area [59].…”
Section: Size Distribution Of Phytoplankton Chlorophyll a Biomass And...mentioning
confidence: 79%
“…Compared to some other Arctic phytoplankton species, Phaeocystis spp. have a wider tolerance toward temperature, as they are also commonly found in the Atlantic ( Hoppe et al, 2018 ), but may only be able to compete against temperate species to a limited degree ( Ahme et al, 2023 ). This increased fitness makes them a possible candidate for gaining importance in the Arctic spring bloom event in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, there has been an increasing number of studies using metagenomics-based methods in the Arctic Ocean, which have revealed common patterns of prokaryotic diversity in this region. Such studies have been conducted in various parts of the Arctic Ocean and Northern Atlantic, including the Barents Sea, the deep Arctic Ocean, including the Eurasian and Canadian Basins, the Chukchi Sea, the Fram Strait, the Greenland Sea and the North Sea [23,24,26,27,[54][55][56][57]. A comparison of the lists of dominant prokaryote groups shows that the most widespread dominants in these communities are representatives of the Polaribacter, SAR11 and SUP05 groups.…”
Section: Discussionmentioning
confidence: 99%
“…The current number of studies examining prokaryotic diversity in the Arctic Ocean water column utilizing metagenomic methods and 16S rRNA metabarcoding is insignificant in comparison to its extensive territory and diverse hydrological conditions [22][23][24][25][26][27][28][29][30]. Nevertheless, the results already obtained allowed to the identification of the major groups of prokaryotes in the Arctic Ocean.…”
Section: Introductionmentioning
confidence: 99%